Pengaruh Reference Group, Variety Seeking dan Price Terhadap Perilaku Brand Switching - Rendy Marduselan Arifyantama; Dewi Noor Susanti (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi, 2021)
This study aims to examine the effect of group reference, variety seeking and price on brand switching on Samsung smartphone consumers to other brands in Kebumen. The sampling method used is a non-probability sampling technique with a purposive sampling method, namely the technique of selecting sample members by considering the conditions that have been set. Respondents in this study were Samsung smartphone users who had changed brands to other brands. This study used descriptive and statistical analysis methods, which were tested for validity, reliability tests, classical assumption tests, and multiple linear regression tests. The test in the t test shows that the reference group has a significant effect on brand switching of Samsung smartphone users to other brands, variety seeking has a significant effect on brand switching, price simultaneously (simultaneously) has a significant effect on brand switching, and group reference, variety seeking and price against brand switching.